Endoscopic Third Ventriculostomy in Previously Shunted Children - Brichtova, Eva (Hindawi Publishing Corporation, 2013)
Endoscopic third ventriculostomy (ETV) is a routine and safe procedure for therapy of obstructive hydrocephalus. The aim of our study is to evaluate ETV success rate in therapy of obstructive hydrocephalus in pediatric patients formerly treated by ventriculoperitoneal (V-P) shunt implantation. From 2001 till 2011, ETV was performed in 42 patients with former V-P drainage implantation. In all patients, the obstruction in aqueduct or outflow parts of the fourth ventricle was proved by MRI. During the surgery, V-P shunt was clipped and ETV was performed. In case of favourable clinical state and MRI functional stoma, the V-P shunt has been removed 3 months after ETV. These patients with V-P shunt possible removing were evaluated as successful. In our group of 42 patients we were successful in 29 patients (69%). There were two serious complications (4.7%)—one patient died 2.5 years and one patient died 1 year after surgery in consequence of delayed ETV failure. ETV is the method of choice in obstructive hydrocephalus even in patients with former V-P shunt implantation. In case of acute or scheduled V-P shunt surgical revision, MRI is feasible, and if ventricular system obstruction is diagnosed, the hydrocephalus may be solved endoscopically.